Residual capacity and the political economy of pandemic response in Ghana - Kofi Takyi Asante (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
On the whole, poor countries in Africa and elsewhere seem to have weathered the coronavirus (SARS-CoV-2, or COVID-19) pandemic better than wealthier countries with superior healthcare systems. Using the Ghanaian case, this paper draws on newspaper articles, policy statements, and other secondary sources to explain how the country's competitive clientelist political settlement mediated the public health outcomes of the pandemic. It argues that while it lacks overall state capacity, Ghana was able to surmount the limitations of its weak and underresourced public health system by leveraging 'residual capacity' from previous public health programmes and a strong proactive response from the continental and subregional organizations. The government's strong early response enabled it to gain control of the situation in the crucial first few months of the outbreak. However, with an upcoming election later in the year and unwilling to bear the political costs of sustaining its initial efforts, the government subsequently wavered in its response. The country's infection and death rates spiked and dipped in response to these waves of enforcement. The paper concludes with a brief discussion of the limits of 'residual capacity' in public service delivery.
Keywords: H40; I15; P16; 330; COVID-19; state capacity; competitive clientelism; political settlements; Ghana; public health